Pengaruh Bahan Baku Halal dan Persepsi Halal terhadap Minat Pembelian Menu KFC di Bandar Lampung dengan Country of Origin sebagai Variabel Mediasi - Mahardi, Yoan Firdaus; Bakti, Dadang Karya; Nugeraha, Prasetya (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
In the context of globalization and increasing consumer awareness of halal food, understanding the factors that influence purchase decisions is crucial. Therefore, this study focuses on how halal raw materials and perceptions affect purchase intention, as well as the role of country of origin in shaping these decisions. This research aims to examine the influence of halal raw materials and halal perceptions on purchase intention, with the country of origin acting as a mediating variable in purchasing KFC menu items in Bandar Lampung. A quantitative approach was used in this research, with data collected through a Google Form questionnaire distributed via social media, involving 97 respondents from Bandar Lampung. The data analysis was performed using Structural Equation Modeling (SEM) PLS. The results of the study indicate that halal raw materials, halal perceptions, and country of origin all have a positive and significant impact on purchase intention for KFC menu items. This suggests that consumers in Bandar Lampung place significant importance on halal aspects when selecting products, and that the country of origin has a positive influence on their purchase decisions. The implications of these findings suggest that KFC should pay more attention to the halal aspects of its ingredients and ensure clear communication about product quality. Additionally, managing the country of origin image effectively can help boost consumer purchase intention.